2012
DOI: 10.1080/03079457.2012.732691
|View full text |Cite
|
Sign up to set email alerts
|

Differential innate responses of chickens and ducks to low-pathogenic avian influenza

Abstract: Ducks and chickens are hosts of avian influenza virus, each with distinctive responses to infection. To understand these differences, we characterized the innate immune response to low-pathogenicity avian influenza virus H7N1 infection in chickens and ducks. Viral RNA was detected in the lungs of chickens from day 0.8 to 7, in ducks mainly at day 4. In both species, viral RNA was detected in the bursa and gut. Infection in chickens resulted in up-regulation of interferon (IFN)-α and IFN-β mRNA, while in the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 46 publications
11
71
1
Order By: Relevance
“…In addition, a recent study revealed that Muscovy ducks (Cairina moschata) mounted overall stronger innate immune response to H9N2 infection than chickens (Huang et al, 2012). Several studies have demonstrated that expression of immune-related genes varied with different types of ducks, different origins of AIV isolates and different tissues Cornelissen et al, 2012;Maughan et al, 2013). Furthermore, age-related differences in immune responses to AIV infection have also reported in chickens and ducks (Reemers et al, 2010;Pantin-Jackwood et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study revealed that Muscovy ducks (Cairina moschata) mounted overall stronger innate immune response to H9N2 infection than chickens (Huang et al, 2012). Several studies have demonstrated that expression of immune-related genes varied with different types of ducks, different origins of AIV isolates and different tissues Cornelissen et al, 2012;Maughan et al, 2013). Furthermore, age-related differences in immune responses to AIV infection have also reported in chickens and ducks (Reemers et al, 2010;Pantin-Jackwood et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the lack of the TLR7 response in the brain and lung of H7N1-infected chickens is related to an inadequate innate response of the host to clear the virus infection. TLR7 may contribute to influenza virus recognition and in chickens and ducks in the PRR's mRNA induction and consequently the induction of cytokine mRNA may influence the host's ability to control HPAI avian influenza, as was found for low-pathogenic avian influenza-infected chickens (Cornelissen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For the quantification, a standard curve of a plasmid containing the cytokine gene of interest in pGEM-T easy (Promega Benelux b.v., Leiden, the Netherlands) was used. Primer sequences for real-time PCR used in this study have been described by Cornelissen et al (2012). The primer pairs for duck and chicken inducible nitric oxide synthase (iNOS) gene (forward, CCACCAGGAGATGTTGAATATGTC; reverse, CCA-GATGTGTGTTTTCCATGCA) have been described by Burggraaf et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As AIV preferentially binds to α-2,3-linked sialic acids (Rogers et al, 1983), we may expect reduced AIV susceptibility of the pigeon. Furthermore, the innate immune response of the host may affect its susceptibility for the establishment of AIV infection (Cornelissen et al, 2012). Different to chickens, pigeons-like ducks, which exhibit a certain natural resistance to AIV-possess the retinoic acid-inducible gene I, which triggers a strong antiviral interferon response (Barber et al, 2010) possibly controlling AIV replication in a sufficient way.…”
Section: Discussionmentioning
confidence: 99%